Manned submersible dives reveal a singular assemblage of Hexactinellida (Porifera) off the Amazon River mouth, Northern Brazil - Moser, Julia; Moraes, Fernando C.; Castello-Branco, Cristiana; Pequeno, Carolline B.; Muricy, Guilherme (Zootaxa, 2022)
The outer shelf and upper slope region under the influence of the Amazon River mouth harbors an extensive reef system with a rich sponge fauna, but no hexactinellids were recorded in the area so far. In this work, manned submersibles were used to describe for the first time three species of Hexactinellida off the Amazon River mouth: Hyalonema (Cyliconemaoida) alucia sp. nov., Dactylocalyx pumiceus and Claviscopulia facunda. We found two morphotypes of Dactylocalyx pumiceus, suggesting that it may be a complex of cryptic species. The populations of the three species off Pará State were sparse, but a large aggregation of D. pumiceus was found off Maranhão State from 145 to 230 m depth. These findings indicate that hexactinellid grounds may be more common along the Northern Brazilian continental outer shelf and slope than previously thought.